An optimum path to obtain beta Cu-Zn-Al by mechanical alloying - Sesma, Fernando Gabriel (2013)
Cu–Zn–Al alloys have been produced by low energy ball milling following six different synthesis paths. In all cases, a mixture of a and b phases have been obtained. Milling for 100 h without interruptions the three elements simultaneously gave the best ratio between the amount of b phase and the milling time. Low temperature thermal treatments to the powders (up to 450 C) lead to c phase crystallite growth, with the amount of b phase remaining nearly constant. With anneals at 800 C the b phase fraction in the powder increased solely to 86%. A sample of pure b phase was obtained only after warm compaction at 680 MPa and sintering at temperatures above 800 C. In addition, it was necessary to reach temperatures of 900 C in order to have a material that transforms martensitically.